Dynamic analysis of the throwing arm in handball - Fradet, L.; Cretual, A.; Delemarche, P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Some recent studies present kinematic parameters such as humeral rotation (Fradet and al. 2000-a), linear velocities (Tillaar and Ettemaa 2003, Fradet and al. 2004), angular velocities (Fradet and al. 2000-b) that are different in handball from those denoted in overarm throwing in other sports. The dynamic parameters could explain these esults. That is the reason why the aim of this study is to analyse the dynamic parameters during handball throwing. Method Twenty handball players took part in this study (height: 1.90 ± 0.05 m, mass: 84.9 ± 11.8 kg). Six of them (age: 25.4 yrs) play in the first french league, seven others in the young french team (age: 17.8) whereas the seven last play in the national league (age: 16.6 yrs). Each player performed four jump-in throws towards a target (from 50cm per 50cm) placed in the middle of the goal. These throws were studied using a Vicon 370 motion capture system (60Hz). Reflective markers were placed over standardized anatomical landmarks in order to identify body segments. The markers positions were filtered using a Butterworth second order low-pass filter. These positions provide us with kinematic data required to compute dynamic parameters. The resultant joint torques and forces are computed using the method described by Feltner and Dapena (1986). The general evolutions of the resultant joint torques and forces are globally similar to those described in study relative to other kind of throwing. However, some specificities can be denoted. Just before ball released, one can indeed observe a horizontal abduction joint torque for some subjects, which does not seem to have ever been obtained in other studies. Moreover, the internal humeral rotation and the abduction torques are lower than those calculated during other kind of throwing. Finally, the maximal joint torques occur earlier in this study comparatively to the other ones. Discussion The lower abduction torques can probably explain the lower external humeral rotation denoted in studies relative to handball throwing. According to the literature, the combination of the overarm horizontal adduction at the beginning of the throw and after that of the overarm abduction induce the humeral external rotation. The internal humeral rotation then observed is only used to control this external rotation. So, for our subjects, the low abduction cannot increase the external humeral rotation what implies a lower internal humeral rotation. To explain why some subjects have a horizontal abduction joint torque just before ball release, we can suggest that it is used to compensate the lower abduction joint torque by restricting the forward elbow progression and facilitating the passing over of the forearm. The precocity of the maximal joint forces and torques could probably explain why the start of the horizontal adduction occurs earlier. We can incriminate also this precocity of the horizontal adduction to explain why the elbow maximal near velocity occurs before the shoulder`s one as it has been observed by Tillaar et Ettemaa (2003).